The impact of potentially modifiable risk factors for stroke in a middle-income area of China: A case-control study - Wu, Yuhang; Chen, Xiaoyun; Hu, Songbo; Zheng, Huilie; Chen, Yiying; Liu, Jie; Xu, Yan; Chen, Xiaona; Zhu, Liping; Yan, Wei (Frontiers in Public Health, 2022)
Aims: To reveal the impact of eleven risk factors on stroke and provide estimates of the prevention potential. Methods: We completed a multicenter case-control study in Jiangxi, China, a middle-income area. Neuroimaging examination was performed in all cases. Controls were stroke-free adults recruited from the community in the case concentration area. Conditional logistic regression and unconditional logistic regression were used for subgroup analysis of stroke type, and other groups (sex, age and urban-rural area), respectively. Odds ratios (ORs) and their population attributable risks (PARs) were calculated, with 95% confidence intervals. Results: A total of 43,615 participants (11,735 cases and 31,880 controls) were recruited from February to September 2018, of whom we enrolled 11,729 case-control pairs. Physical inactivity [PAR 69.5% (66.9%-71.9%)] and hypertension [53.4% (49.8%-56.8%)] were two major risk factors for stroke, followed by high salt intake [23.9% (20.5%-27.3%)], dyslipidemia [20.5% (17.1%-24.0%)], meat-based diet [17.5% (14.9%-20.4%)], diabetes [7.7% (5.9%-9.7%)], cardiac causes [5.3% (4.0%-6.7%)], alcohol intake [4.7% (0.2%-10.0%)], and high homocysteine [4.3% (1.4%-7.4%)]. Nine of these factors were associated with ischemic stroke, and five were associated with intracerebral hemorrhage. Collectively, eleven risk factors accounted for 59.9% of the PAR for all stroke (ischemic stroke: 61.0%; intracerebral hemorrhage: 46.5%), and were consistent across sex (men: 65.5%; women: 62.3%), age (≤55: 65.2%; >55: 63.5%), and urban-rural areas (city: 62.2%; county:65.7%). Conclusion: The 11 risk factors associated with stroke identified will provide an important reference for evidence-based planning for stroke prevention in middle-income areas. There is an urgent need to improve awareness, management and control of behavioral and metabolic risk factors, particularly to promote physical activity and reduce blood pressure.